2020
DOI: 10.1155/2020/6174936
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Rehabilitation Can Improve the Functional Capacity and Quality of Life for Pneumoconiosis Patients: A Systematic Review and Meta-Analysis

Abstract: This study evaluated the efficacy and safety of pulmonary rehabilitation (PR) for pneumoconiosis. We systematically searched PubMed, Embase, The Cochrane Library, Web of Science, SinoMed, CNKI, VIP databases and Wanfang Data from their inception to June 1, 2019. A systematic review and meta-analysis of randomized controlled trials (RCTs) of PR for pneumoconiosis was conducted and reported in compliance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Two reviewers independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 32 publications
(32 reference statements)
0
10
0
1
Order By: Relevance
“…Pneumoconiosis patients' healthy transition and life reconstruction experiences in the CBPR program are congruent with former PR-related studies revealing patients' PR experience in terms of reduced symptoms, improved physical, mental, emotional, and social function, enhanced sense of control, and increased disease management ability. [25][26][27] Pneumoconiosis patients reported improvements in their mental state, physical capacity, mobility, and daily activities, which corroborated the quantitative evidence regarding PR's effectiveness in improving physical functional capacity, 15,16 psychological symptoms, 28 and QoL 16 for patients with chronic respiratory diseases. In this study, pneumoconiosis patients also delightfully reported their active social life in the CBPR program.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Pneumoconiosis patients' healthy transition and life reconstruction experiences in the CBPR program are congruent with former PR-related studies revealing patients' PR experience in terms of reduced symptoms, improved physical, mental, emotional, and social function, enhanced sense of control, and increased disease management ability. [25][26][27] Pneumoconiosis patients reported improvements in their mental state, physical capacity, mobility, and daily activities, which corroborated the quantitative evidence regarding PR's effectiveness in improving physical functional capacity, 15,16 psychological symptoms, 28 and QoL 16 for patients with chronic respiratory diseases. In this study, pneumoconiosis patients also delightfully reported their active social life in the CBPR program.…”
Section: Discussionmentioning
confidence: 53%
“…14 Recent quantitative studies have validated PR's effect on pneumoconiosis patients' lung function, physical performance, and health-status outcomes. 15,16 However, qualitative evidence regarding PR's impact on pneumoconiosis patients' health and lives is lacking in the literature. Therefore, this study applied a qualitative approach to address this knowledge gap by exploring pneumoconiosis patients' experience in a CBPR program.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary rehabilitation (PR) for patients diagnosed with ILD are delivered in different settings and models. Traditionally, PR programs are center-based and shown positive outcomes in sarcoidosis ( 34 ) and pneumoconiosis patients ( 35 ). IPF patients have improved maximum exercise capacity and reported less shortness of breath and better quality of life after rehabilitation ( 36 ).…”
Section: Pr Delivered In Ildsmentioning
confidence: 99%
“…These concerns may be particularly relevant in those patients undergoing home rehabilitation or telerehabilitation ( 60 ). Additionally, a recent meta-analysis considered the main limitation was the total absence of exacerbations and adverse events reported during rehabilitative programs in the majority of studies published ( 35 ). Considering that adverse outcomes are extremely varied, it is expected that in the future, new studies will focus on more objective criteria such as: the number of patients who were unable to maintain saturation above 88% during exercise sessions (even using oxygen supplementation), electrocardiographic abnormalities (in particular, the appearance of atrial and/or ventricular arrhythmias during or after exercise) ( 61 ), amount of oxygen administered, levels of dyspnea reported during sessions, as well as their relationship with possible adverse events, such as: exacerbations, need for medication changes and new visits to the doctor, number of hospitalizations, cardiovascular events ( 62 ), fractures, skeletal muscle injures, and deaths during the study ( 36 ).…”
Section: Safety Of Exercise Training For Ildsmentioning
confidence: 99%
“…5,9,12 또한 진폐증으로 인한 호흡기능 저하를 향 상시킬 수 있는 치료적 중재 방법에 대한 연구도 많이 보고되고 있 다 30,31. 하지만, 고령의 진폐 환자가 보이는 호흡기능의 저하가 인지기…”
unclassified